Shaping The Future Of The Architectural Profession - Mohamed Khaidzir, Khairul Anwar (Faculty of Built Environment, 2004)
The intricacies of the design and construction processes when compared to the linear and predictable operations of a vehicle production line have created a building industry that is unique in almost every aspect of its conception, planning, management and realisation. In addition, other influential factors such as the boom and bust cycle of the market economy, the growth of advanced construction technologies and techniques and the increasing level of specialisation within its constituent professions and building trades continuously reshape the landscape of the industry, particularly in Malaysia. Considering such a scenario, rapid changes are envisaged that may re-shape the overall structure and undertakings of the building industry. This paper looks into the outline development of the architectural profession in the past decade for the hope of identifying several issues that may determine the relevancy of current practices of the architectural profession.